Ominous‐appearing papulonodules in the genitocrural area. (1st December 2021) - Kumar, S.; Batrani, M.; Kapoor, P.; Kaur, N.; Kubba, A.
Abstract: Click https://wileyhealthlearning.com/#/online-courses/aafc73a0-ecce-4902-8f2c-a63e3df75ece for the corresponding questions to this CME article.